Radiation therapy in the management of Merkel cell carcinoma: current perspectives. (August 2011) - Rush, Zoe; Fields, Ryan C; Lee, Nancy; Brownell, Isaac
Merkel cell carcinoma (MCC) is a rare cutaneous neuroendocrine neoplasm with a propensity for metastatic spread. When managing MCC, surgical excision is often the initial treatment. As MCC is generally radiosensitive, many institutions include adjuvant radiation therapy (RT) in their standard treatment protocols. In the absence of prospective randomized clinical trials, a number of retrospective reports suggest that adjuvant RT can improve local and regional recurrence rates. Here, we provide an overview of recent studies on the use of RT in MCC treatment and explore the limits of the current knowledge. Ultimately, the benefits and risks associated with using RT in the treatment of MCC remain poorly described and merit more rigorous investigation.